THE EFFECT OF DIGITAL BANKING SERVICES ON CUSTOMER GROWTH - Yusupov Ulug‘bek Mamayusupovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study examines the effect of digital banking services on customer growth in the financial sector. In recent years, the rapid development of financial technologies has significantly transformed traditional banking systems, making services more accessible, faster, and more efficient. Digital banking tools such as mobile banking applications, online payment systems, internet banking platforms, and electronic wallets have become key drivers of customer acquisition and retention.